PENGARUH KINERJA KEUANGAN, KEBIJAKAN HUTANG DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Wirdha, Fitriah; Afandi, Agus (Publika Citra Media, 2025)
This research aims to determine the influence of financial performance, debt policy, investment decisions on the value of banking sector companies listed on the Indonesia Stock Exchange (BEI). The research period carried out was the 2019-2023 period. The type of research used is quantitative research with secondary data. Determining the sample for this research used a purposive sampling method and was based on criteria obtained from 12 (twelve) samples of companies listed on the Indonesia Stock Exchange (BEI). and analyzed using panel data regression techniques with random effect models to test the hypothesis. Hypothesis testing in this study uses multiple linear regression with Eviews version 13. The results of this study show that simultaneously the financial performance variables, debt policy and investment decisions have an effect on company value, partially financial performance variables have an effect on company value, debt policy has an effect on company value, while investment decisions have no effect on company value.